Control interno de la cuenta de inventarios y su incidencia en la rentabilidad de la empresa ferri muebles edimca, periodo 2021-2022. - Campuzano Galarza, Milena Nahomy (2024)
Each company needs to implement an internal control system that guarantees constant supervision of its inventories. The company Ferri Muebles EDIMCA, specialized in the sale and custom solutions in wood, accessories for the furniture and construction industry, was founded in 2003 and has experienced a decline in its economic activity due to the deficiency of effective internal control of your inventory. The objective of this research is to evaluate the incidence of internal control of the inventory account on the profitability of the company Ferri Muebles Edimca during the period 2021 to 2022. To carry out this study, various research approaches were used, including correlational, descriptive and longitudinal research. In addition, deductive and analytical methods will be applied to define the population and the appropriate sample. Regarding the results obtained, in the first specific objective, interviews with the warehouseman and internal control questionnaires are applied to the company's accounting department; for the second specific objective, the risks associated with weaknesses in the production control systems are examined. inventories and finally a comparison was made of the evolution of the financial profitability obtained in the study period of the company. At the conclusion of the research, conclusions and recommendations were formulated supported by the corresponding bibliography and relevant annexes that complement the understanding of the study.